1999
DOI: 10.1021/la9808667
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Benzenethiolate and Benzyl Mercaptide on Au(111)

Abstract: We report the results of theoretical studies on the self-assembled monolayers of benzenethiolate (BT) and benzyl mercaptide (BZM) on a Au(111) surface. A few relevant potential energy parameters were determined. We have performed annealing type molecular dynamics simulations where the minimized initial configurations are heated to 1000 K and then cooled to room temperature, assuming two types of unit cells:  √3 × √3R30° and 2 × 2. The results of the simulations showed that BZM formed a nearly perfect herringbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 31 publications
7
108
0
Order By: Relevance
“…Several earlier studies found that benzenethiol do not form an ordered structure on gold surface [42,70,71]. Formation of small ordered domains was also reported for benzenethiol SAMs [72]. In a different study, the ( ffiffiffiffiffiffi 13 p  ffiffiffiffiffiffi 13 p Þ structure was also reported [73].…”
Section: W Azzam / Materials Chemistry and Physics XXX (2016) 1e8mentioning
confidence: 78%
“…Several earlier studies found that benzenethiol do not form an ordered structure on gold surface [42,70,71]. Formation of small ordered domains was also reported for benzenethiol SAMs [72]. In a different study, the ( ffiffiffiffiffiffi 13 p  ffiffiffiffiffiffi 13 p Þ structure was also reported [73].…”
Section: W Azzam / Materials Chemistry and Physics XXX (2016) 1e8mentioning
confidence: 78%
“…Within these monolayers, the biphenyl based monomers adopt more upright than prostrate orientations on the underlying Au [46] and, importantly, exhibit closely comparable molecular tilt angles to 4-MBA. Molecular dynamics simulations conducted by Jung et al [47] illustrate that molecules of benzyl mercaptan adsorbed on Au(111) in herringbone-like SAM arrangements would also have similar tilt angles to 4-MBA. Hence, it is probable that monolayers of 4-MBA adopt a herringbone-like packing scheme.…”
Section: Resultsmentioning
confidence: 99%
“…• unit cells (18). Guided by the above implications, we examined the adsorption behavior of 1,4-benzenedithiol (1,4-BDT) on gold and silver sol surfaces by means of surface-enhanced Raman scattering (SERS).…”
Section: Introductionmentioning
confidence: 99%